The house on the strand. - Du Maurier, Daphne, 1907-1989. (Garden City, N.Y., Doubleday, 1969)
A young man experimenting with hallucinogenic drugs travels back and forth in time between 14th-century andmodern day England.
Keywords: Detective and mystery stories; Time travel -- Fiction; Cornwall (England : County) -- Fiction; Psychological fiction; Fantasy fiction